2018
DOI: 10.1111/neup.12512
|View full text |Cite
|
Sign up to set email alerts
|

Dynactin is involved in Lewy body pathology

Abstract: Dynactin forms a protein complex with dynein that retrogradely transports cargo along microtubules. Dysfunction of this dynein-dynactin complex causes several neurodegenerative diseases such as Perry syndrome, motor neuron diseases and progressive supranuclear palsy. Recently, we reported colocalization of phosphorylated α-synuclein (p-SNCA) and the largest subunit of dynactin (DCTN1) in Lewy body (LB)-like structures in Perry syndrome. Previous reports have not focused on the relationship between dynactin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Dynactin is part of a dynactin-dynein-complex (DDC), which is responsible for axonal transport and for the passage of cytoplasmic vesicles 77 . The DDC also affects α-synuclein aggregation, and dynactin dysregulation increases Lewy body formation in different brain regions 78 . In this study, we found reduced dynactin 2 expression in the MP of psA30P mice, suggesting for the first time that this decrease is associated with a reduced axonal transport of motor proteins in the gut at early stages of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Dynactin is part of a dynactin-dynein-complex (DDC), which is responsible for axonal transport and for the passage of cytoplasmic vesicles 77 . The DDC also affects α-synuclein aggregation, and dynactin dysregulation increases Lewy body formation in different brain regions 78 . In this study, we found reduced dynactin 2 expression in the MP of psA30P mice, suggesting for the first time that this decrease is associated with a reduced axonal transport of motor proteins in the gut at early stages of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Dynactin is, as a part of the dynactin-dynein-complex (DDC), responsible for axonal transport, and the passage of cytoplasmic vesicles [82], and it affects α-synuclein aggregation increases Lewy body formation in different brain regions [83]. In this study, we found reduced dynactin 2 expression in the MP of psA30P mice, suggesting a reduced axonal transport of motor proteins in the gut at early stages of PD.…”
Section: Discussionmentioning
confidence: 53%
“…Several groups have linked HDAC6 to Lewy body formation and have shown that HDAC6 is a constituent of Lewy bodies 1,5,24 . A role for dynactin was also described in Lewy body formation 25 .…”
Section: Discussionmentioning
confidence: 96%